Catalyzing sustainable fisheries management through behavior change interventions. Issue 5 (15th April 2020) - McDonald, Gavin; Wilson, Molly; Veríssimo, Diogo; Twohey, Rebecca; Clemence, Michaela; Apistar, Dean; Box, Stephen; Butler, Paul; Cadiz, Fel Cesar; Campbell, Stuart J.; Cox, Courtney; Effron, Micah; et al.
Abstract: Small‐scale fisheries are an important livelihood and primary protein source for coastal communities in many of the poorest regions in the world, yet many are overfished and thus require effective and scalable management solutions. Positive ecological and socioeconomic responses to management typically lag behind immediate costs borne by fishers from fishing pressure reductions necessary for fisheries recovery. These short‐term costs challenge the long‐term success of these interventions. However, social marketing may increase perceptions of management benefits before ecological and socioeconomic benefits are fully realized, driving new social norms and ultimately long‐term sustainable behavior change. By conducting underwater visual surveys to quantify ecological conditions and by conducting household surveys with community members to quantify their perceptions of management support and socioeconomic conditions, we assessed the impact of a standardized small‐scale fisheries management intervention that was implemented across 41 sites in Brazil, Indonesia, and the Philippines. The intervention combines TURF reserves (community‐based territorial use rights for fishing coupled with no‐take marine reserves) with locally tailored social‐marketing behavior change campaigns. Leveraging data across 22 indicators and 4 survey types, along with data from 3 control sites, we found that ecological and socioeconomic impacts varied and that communities supported the intervention and were already changing their fishing practices. These results suggest that communities were developing new social norms and fishing more sustainably before long‐term ecological and socioeconomic benefits of fisheries management materialized. Abstract : Article impact statement : Moving from overfishing to sustainability, behavior change campaigns can be used to transition fisheries from near‐term losses to long‐term gains. Abstract : Catalización del Manejo de Pesquerías Sustentables por medio de Intervenciones de Cambio de Comportamiento Resumen: Las pesquerías a pequeña escala son un sustento importante y la principal fuente de proteína para las comunidades costeras en muchas de las regiones más pobres del mundo, sin embargo, muchas sufren de sobrepesca y por lo tanto requieren soluciones de manejo efectivas y escalables. Las respuestas ecológicas y socioeconómicas positivas al manejo generalmente se retrasan con respecto a los costos inmediatos asumidos por los pescadores a partir de las reducciones de la presión ocasionada por la pesca necesarias para la recuperación de la pesquería. Estos costos a corto plazo son un reto para el éxito a largo plazo de las intervenciones. Sin embargo, la mercadotecnia social puede incrementar las percepciones de los beneficios del manejo antes de que se conozcan por completo los beneficios ecológicos y socioeconómicos, lo que genera nuevas normas sociales y finalmente un cambio en el comportamiento a largo plazo. Realizamos censos submarinos visuales para cuantificar las condiciones ecológicas y censos domésticos a los miembros de la comunidad para cuantificar sus percepciones del apoyo al manejo y de las condiciones socioeconómicas. Con esto, evaluamos el impacto de la intervención de manejo para pesquerías estandarizadas a pequeña escala que fue implementada en 41 sitios de Brasil, Indonesia y las Filipinas. La intervención combina las reservas TURF (derechos de uso de pesca territorial basados en la comunidad acoplados con reservas marinas con restricción de pesca) con campañas de mercadotecnia social para el cambio de comportamiento ajustadas al contexto local. Con la movilización de datos a lo largo de 22 indicadores y cuatro tipos de censos, junto con los datos de tres sitios de control, encontramos que los impactos ecológicos y socioeconómicos variaron y que las comunidades apoyaban la intervención y ya se encontraban cambiando sus prácticas de pesca. Estos resultados sugieren que las comunidades ya estaban desarrollando nuevas normas sociales y pescando de manera más sustentable antes de que los beneficios ecológicos y socioeconómicos a largo plazo del manejo de las pesquerías se materializaran. 摘要: 小型渔业是世界上许多最贫困地区沿海社区的重要生计和主要蛋白质来源, 但许多地区存在着过度捕捞的现象, 因此需要制定有效且灵活的管理方案以应对这一问题。管理措施产生的积极的生态及社会经济响应通常滞后于渔民为渔业恢复需要减少捕捞压力而承担的直接成本。这些短期成本压力给干预措施的长期成功带来挑战。然而, 在生态和社会经济效益完全实现之前, 社会营销或有助于增进对管理效益的认知, 从而推动建立新的社会规范, 并最终实现长期可持续的行为改变。我们通过水下观测量化了水体生态条件, 并通过社区成员家庭调查量化了他们对管理支持和社会经济条件的看法, 从而评估了在巴西、印度尼西亚和菲律宾的 41 个地点实施的标准化小型渔业管理措施的影响。这些管理措施结合了 TURF 保护区 (基于社区的渔业捕捞领土使用权与禁止捕捞的海洋保护区) 与适应当地情况的行为改变社会营销活动。我们利用 22 项指标和 4 种调查类型的数据, 加上来自 3 个对照位点的数据, 发现管理对生态和社会经济的影响各不相同, 此外, 社区成员支持干预措施并已经改变他们的捕捞方式。这些结果表明, 在渔业管理的长期生态及社会经济效益实现之前, 社区已开始发展新的社会规范, 并以更可持续性的方式开展渔业活动。【翻译: 胡怡思; 审校: 聂永刚】